Engaging Young Audiences Before, During and After the Lockdown - Catalani, Anna; Hughes, Heather (Museum and Society, 2020)
This short article focuses on two heritage sites (the International Bomber Command Centre and Creswell Crags) and reflects on the ways in which such medium-size institutions are trying to find ways of maintaining offsite engagement with young audiences while at the same time generating revenues.